ASSOCIATION MAPPING OF QUALITY TRAITS WITH SSR MARKERS IN TALL FESCUE (FESTUCA ARUNDINACEA SCHREB.) - + + Y. Lou; X. Sun; Y.Chao; E.Amombo; H.Wang; F.Song; Q.Xu; Y. Zhuge (Journal of Animal and Plant Sciences, 2018)
Identification of the association between molecular markers and quality traits would promote the efficient utilization, conservation and management of the tall fescue germplasm. Thus, 59 tall fescue accessions from different origins (16 cultivars; 19 from America; 15 from Europe; 2from Africa and 7 from Asia), were evaluated for quality traits and genetic diversity with 90 simple sequence repeat (SSR) markers. Significant variations were observed among 59 tall fescue accessions in dry matter (DM), crude protein ( CP), crude fat ( CF),and CP were negatively correlated withDM (r=0.269) and CF (r=0.254), respectively. Three sub-populations were identified within the collections but no obvious relative kinship ( K) was found. The GLM model was used to describe the association between SSR markers and quality traits. 41 SSR markers associated with quality traits were observed. In addition, 26 markers were significantly associated with CP; 12 markers with CF and 4 markers with DW. Notably, M100 marker was significantly both associated with CF and DM. Moreover, six significant associations were observed between CP and M213, M214, M215, M217, M218, and M216 markers, and the explained ratio of genetic variation were exceed 20 %. These identified marker alleles associated with quality traits could provide important information and markers for molecular-assisted breeding in tall fescue. effective utilization. In order to provide a reasonable
Keywords: Association mapping; SSR; Tall fescue; Quality traits.